PERAN PENDIDIKAN AGAMA DI SEKOLAH LATANSA CENDIKIA DI ERA MODERNISASI SEBAGAI UPAYA PEMBENTUKAN KARAKTER BAIK - Afifah, Zalfa (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2024)
This study aims to understand in depth the role of religious education in shaping the character of students at Sekolah Latansa Cendikia. This research is a qualitative study with a case study approach. The results show that Sekolah Latansa Cendikia applies three strategies in character education based on religion. First, inculcation of character through religious activities such as praying, performing duha prayer, reciting the Qur'an, and performing congregational Dhuhr prayers, both during face-to-face learning and distance learning during the COVID-19 pandemic. Second, the support and active role of the principal in the success of the character education program. Third, exemplary provision by the principal and teachers in being disciplined, honest, polite, independent, and responsible. The implication of this character education program is that students are accustomed to being disciplined, responsible, and thinking before acting.